2005
DOI: 10.1172/jci25350
|View full text |Cite
|
Sign up to set email alerts
|

Natural peptides selected by diabetogenic DQ8 and murine I-Ag7 molecules show common sequence specificity

Abstract: In this study, a large number of naturally processed peptides was isolated and identified from the human diabetes-susceptible class II MHC molecules HLA-DQ8 (DQA1*0301,DQB1*0302) and from murine I-A g7 species, both of which are expressed in genetically identical APC lines. The peptides presented during the processing of autologous proteins were highly selective in showing sequence specificity, mainly consisting of 1 or more acidic residues at their C terminus. Testing for binding to the MHC molecules revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
147
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(157 citation statements)
references
References 42 publications
8
147
2
Order By: Relevance
“…12 As for I-A g7 and DQ8, this pocket also accepted Gln, Asn and Gly. 12,27 The decrease of Arg, Lys and Pro at P9 confirmed previous the data for non-Asp b57 alleles, 27 suggesting that these amino acids at P9 would negatively interfere with the peptide binding to DR8. An interesting result concerned the positions P4 and P6, with a clear preference for Lys: 46% of the peptides had Lys at P4 or P6.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…12 As for I-A g7 and DQ8, this pocket also accepted Gln, Asn and Gly. 12,27 The decrease of Arg, Lys and Pro at P9 confirmed previous the data for non-Asp b57 alleles, 27 suggesting that these amino acids at P9 would negatively interfere with the peptide binding to DR8. An interesting result concerned the positions P4 and P6, with a clear preference for Lys: 46% of the peptides had Lys at P4 or P6.…”
Section: Resultsmentioning
confidence: 83%
“…9 The absence of Asp at b57 is related to the preference of these alleles for the binding of acid residues in the P9 pocket. [10][11][12][13] This common feature, known to be involved in clinical disease 14,15 is also found in HLA-DR8, with Ser at b57, but not in the DQ4 (DQA1*0401/DQB1*0402), molecule of the DR8 haplotype that has an Asp at b57.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Since I-A g7 and DQ8 were noticeably SDS-unstable it was proposed that they must bind promiscuously and to low affinity peptides [16]. However, mass-spectrometry based identification of naturally processed peptides selected by I-A g7 and DQ8 generated very different results: both the murine and human alleles selected for similar peptides with a very well defined binding motif characterized by multiple C-termini acidic amino acids [17,[24][25][26].…”
Section: Biochemical Structural and Functional Properties Of Diabetementioning
confidence: 99%
“…Binding studies demonstrated that the acidic amino acids interacted with the P9 pocket and contributed significantly towards binding affinity [24,25]. And moreover, the specificity of the P9 pocket, composed of the non-Asp β57 residue, was crucial in determining selection of peptides [24,26].…”
Section: Biochemical Structural and Functional Properties Of Diabetementioning
confidence: 99%